Tube Thoracostomy: Complications and Its Management - Emeka B. Kesieme; Andrew Dongo; Ndubueze Ezemba; Eshiobo Irekpita; Nze Jebbin; Chinenye Kesieme (Pulmonary Medicine)
Background. Tube thoracostomy is widely used throughout the medical, surgical, and critical care specialities. It is generally used to drain pleural collections either as elective or emergency. Complications resulting from tube thoracostomy can occasionally be life threatening. Aim. To present an update on the complications and management of complications of tube thoracostomy. Methods. A review of the publications obtained from Medline search, medical libraries, and Google on tube thoracostomy and its complications was done. Results. Tube thoracostomy is a common surgical procedure which can be performed by either the blunt dissection technique or the trocar technique. Complication rates are increased by the trocar technique. These complications have been broadly classified as either technical or infective. Technical causes include tube malposition, blocked drain, chest drain dislodgement, reexpansion pulmonary edema, subcutaneous emphysema, nerve injuries, cardiac and vascular injuries, oesophageal injuries, residual/postextubation pneumothorax, fistulae, tumor recurrence at insertion site, herniation through the site of thoracostomy, chylothorax, and cardiac dysrhythmias. Infective complications include empyema and surgical site infection. Conclusion. Tube thoracostomy, though commonly performed is not without risk. Blunt dissection technique has lower risk of complications and is hence recommended.